Indre mod Ydre Europa: Irak-konflikten 2003 og Europas geopolitiske puslespil - Hans Mouritzen; Anna Riis Hedegaard (Danish Institute for International Studies (DIIS), 2004)
– The paper maps practically all European states between, on the one hand, the US and UK belligerents in the Iraq operation 2003 and, on the other hand, their main critics France, Germany, and Russia. We describe these patterns and tentatively try to explain them. Whereas we reject public opinion, government ideology or state capability (small state vs. great power) as explanations, a geopolitical explanation turns out to account much better for the observed pattern. A political conflict between inner and outer Europe is a future possibility.
Keywords: 330; Geopolitik; Irak; Europa